Macroprudential Intermediation Instruments Policy on Mitigating Risk Management Sharia Bank in Indonesia - Putri Fariska; Ajeng Luthfiyatul Farida; Mochamad Malik Akbar Rohandi (Universitas Islam Bandung, 2023)
Sharia banks must face various operational risks, including shifting from macroeconomic, regulatory factors. The central bank has set minimum policies that must be met by sharia banking in managing risk management so that bank operations can run consistently and prudently under sharia principles. During the pandemic, the central bank has issued stimuli to maintain stability in the financial services sector through a financing restructuring policy for the increase in defaults in the economic recession in Indonesia. And also issued a policy to regulate the Macroprudential Intermediation Ratio to mitigate the impact of increasing risks on the domestic economy. Previous studies stated that macroprudential policies could reduce banks' risk level, but lack of research on Islamic banks. So this study aims to examine the Effectiveness Macroprudential Intermediation Instruments Policy on Mitigating Risk Management Sharia Bank. Using Vector Autoregression and Impulse Response to capture short and long-term impacts along with a causal relationship from 2015 to 2021. This study indicates that the Macroprudential Intermediation Policy effectiveness affects financing and liquidity risks. There's a causal relationship between the Macroprudential Intermediation Policy and financing risk and vice versa, but not in liquidity risk. The response due to shocks between the Macroprudential Intermediation Policy, financing risk, and liquidity risk are not convergent except in the short-term mismatch ratio. So, managing Effectiveness Macroprudential Intermediation Instruments Policy on Mitigating Risk Management Sharia Bank is vital for Islamic banking, because if a shock occurs in this process, the impact will occur in the long term and can lead to bankruptcy.